Spatial Awareness, Intersectionality, and the Campus Map: Centralizing Space in Equity, Diversity, and Inclusion - Mizzi, Robert; Akbari, Ehsan; Zargarian, Tannaz; Yendt, Christopher (Canadian Journal of Higher Education, 2026)
Canadian universities continue to strive to promote equity, diversity, and inclusion (EDI) in higher education through their policies and programs. While these efforts can increase access and reduce discrimination and inequity facing marginalized students, critiques highlight these efforts as being overly simplistic or too generic. Further, the current literature around EDI discourses pays little attention to the spatial dimensions of marginalization. This project aims to identify how campus geography contributes to students’ experiences of oppression and inclusion. For this study, 22 students from diverse backgrounds were recruited from three Manitoba universities and interviewed about their experiences of marginalization, with a particular focus on how campus spaces shape identity and belonging. The findings suggested that (a) multiplicity is erased in participants’ interpretations of campus spaces, (b) spatial and social diversity shape student involvement, and (c) access and accessibility remain an ongoing concern. Based on these findings, the authors argue that an intersectional spatial analysis can potentially assist EDI efforts at Canadian universities.